The Governance of Covid-19 Pandemic Health Emergency in Italy: A Constitutional Perspective - Cossiri, Angela (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
The essay focuses on the measures that have been taken in Italy to limit the contagion with Coronavirus in the first phase of the health emergency in 2020. The Italian Government was the first to face the epidemiological crisis in a constitutional democracy. The lockdown was one of the most drastic in Europe. On the one hand, fundamental freedoms of individuals have been compressed; on the other, the objective of limiting the expansion of the contagion in the early stage of pandemic expansion has been achieved, probably saving all European countries from an ungovernable health crisis before a minimal preparation. Even some critical aspects in the decision making process could be highlighted from a constitutional law perspective, the Author believes that the temporary measures, although drastic, not exceeded the limits allowed by the Italian Constitution, nor they seriously affected the balance between the powers at least in the first/second phase. The majority of Parliament approved ex post the law-decrees adopted by the Council of Ministers, demonstrating that it share the Government’s political position. Furthermore, in a very short time, the Italian people, in their vast majority, spontaneously adapted to the imposed prohibitions, demonstrating a sense of responsibility and solidarity towards the most vulnerable categories with respect to the effects of the virus (elderly and sick people, for example). The reasons of the economy, which would have required not to stop business activities, have been temporarily recessive with respect to the protection of the health of the community. This decision seems to find its ultimate foundation in the Article 2 of the Italian Constitution which requires everyone to respect the duty of social solidarity.